PENGALIHAN FUNGSI HARTA TANAH WAKAF: Analisis Terhadap UU No. 41 Tahun 2004 dan KHI - Amsanul Amri; Rodhatul Wardhani (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2018)
Waqf is the property of Muslims whose benefits and functions can be used by Muslims to improve the economy of the people. Endowments in the context of this study are limited to the object of study of waqf land. The main problem in this study is the transfer of the function of waqf land assets, where practically many waqf lands do not function, so that economical smart solutions are needed with the mechanism of revitalization of waqf land to maximize its function in improving the economy of the people. This study uses the research library research method by conducting a legal analysis of Law No. 41 of 2004 concerning Endowments and Compilation of Islamic Law ratified from Islamic Fiqh. The results of this study are, the transfer of waqf property functions is permitted by Hanafi and Hanbali priests, but is not permitted by the Syafi'iyyah clerics. Among the scholars who did not allow the transfer of the functions of the waqf property, namely Imam an-Nawawi and as-Suyuthi who argued, that the waqf property should only be used in accordance with lafadz and the first goal said by the wakif. Whereas according to the positive law, may transfer the waqf property to the public interest and not violate the Shari'ah. This is stated in Law No. 41 of 2004 concerning Waqf, PP No. 41 of 2006, KHI Book III Article 225, Qanun Aceh No. 10 of 2007, and PBWI No. 1 of 2008. There was a difference of opinion between Islamic law from among Syafi'iyyah scholars and positive law.